Role of obturator in restoring quality of life and function in maxillary oncological defect cases- A systematic review - Neelima Manoj; Ahila Singaravel Chidambaranathan; MuthuKumar Balasubramanium; Ganesh RamKumar Rajapandi (Oral Oncology Reports)
Statement of problem: Whether prosthetic rehabilitation significantly affects quality of life and functions of post maxillectomy patients. Objective: Systematically analyze the effects of different types of obturators on post-maxillectomy patients focusing on quality of life and function. Materials and methods: An electronic search was conducted across four databases PubMed, Google Scholar, Cochrane Library, and ScienceDirect in English language from January 1995 June 2024 using the key terms maxillectomy OR hemi-maxillectomy OR palatomaxillary defect OR Aramany OR Brown OR Okay AND obturator OR denture OR prosthetic AND flap OR surgery OR prosthetic rehabilitation. Additionally, a hand search was performed in the institutional library on Journal of Prosthetic Dentistry, Journal of Indian Prosthodontic Society, Journal of Prosthodontics, International Journal of Prosthodontics and Indian Journal of Prosthodontic Research. Results: Seven articles were included in this systematic review. Patient scores from quality-of-life questionnaires and functional ability evaluations were compared across a total of 251 patients, including those with and without obturators. The evaluation included 3 prospective studies, 2 retrospective studies, 1 clinical study, and 1 randomized controlled trial. The results demonstrated a statistically significant improvement in both speech and quality of life for patients using maxillary obturators. Conclusion: Obturator prostheses are not only improved the health-related quality of life (HRQOL) but also enhance overall function of the patient rehabilitated with maxillary oncological defects. They play a crucial role in orofacial rehabilitation by addressing functional and aesthetic challenges faced by individuals with such defects. This positive impact is likely due to the prostheses' ability to restore oral and facial functions, improve speech, and enhance self-esteem and social interactions.